Analisis Penggunaan Media Gambar Berseri Untuk Meningkatkan Kemampuan Membaca Siswa Disleksia Di Sekolsh Dasar - Arif Widodo; Dyah Indraswati; Agam Royana (Universitas Wahid Hasyim Semarang, 2020)
Abstract Children with special needs require different learning services with children in general. One kind of children with special needs is a child who has difficulty in learning and it is called dyslexia. Generally, children with dyslexia have some difficulties in learning and one of it is difficulty reading. The study aims to analyze the use of radiant images as media in reading for Dyslexia children. The subject in this study is Dyslexia students grade IV at SDN Repok Puyung. The methods used in this study is qualitative descriptive. Data collection was conducted through reading and observation tests. Data presented in the form of diagrams, then analyzed descriptively. The main problem in this research is whether the serial image media can help Dyslexia students in improving their reading skill. The results showed that the use of serial image media could improve their reading skill. The increasing of reading skills as reaction for memory improvement of Dyslexia student through pictures. Other findings in this study are improvement in learning activity and reading motivation for Dyslexia students.